166 - CURRICULUM AND SCHOOL'S CONTENTS: SELECTION AND CRITERIA PREFERRED BY TEACHERS OF MUNICIPAL SCHOOL DISTRICT OF VILA VELHA- ES (Fiep Bulletin - online, 2011)
The paper attempts to identify the criteria used by teachers of Physical Education in the choice of content to develop the curriculum of the discipline. The paper also attempts to investigate which knowledge is considered valid, important or essential for teaching Physical Education. This study is qualitative and exploratory, using as a tool a semi-structured interviews, which were applied to 14 elementary school teachers (5th to 8th grades) working in the Municipal School district of Vila Velha – ES. The main results and conclusions identified that the participants teachers are unanimous in their report that they work with team sports; And in this sense the research questions how the student is considered in this selection of content, and how the student's interest is situated with regard to access to other knowledge of the area of Physical Education.
Keywords: curriculum; content; physical education teacher